A Reproducible Computational Framework for Integrated Kinematic Analysis of Serial Robotic Manipulators - Thammarat Yawisit; Perapat Pattanawanichchakorn; Thanayut Supachart; Prapart Ukakimaphan (Zenodo (CERN European Organization for Nuclear Research), 2026)
This work presents a reproducible computational framework for integrated kinematic analysis of serial robotic manipulators. The framework reconstructs a multi-sheet workbook into a structured computational system supporting forward kinematics, inverse kinematics, workspace sampling, trajectory analysis, and real-time visualization. The demonstrator system is a 4-DOF serial manipulator with DH parameterization. The framework evaluates 10,530 workspace configurations and reconstructs a multi-frame trajectory with a cumulative path length of approximately 1012 mm. This work emphasizes computational transparency, reproducibility, and educational interpretability, bridging the gap between symbolic kinematics and geometric intuition. This manuscript is released as a preprint and is currently being prepared for submission to a peer-reviewed journal.
Keywords: Robotic Mechanisms and Dynamics; Robot Manipulation and Learning; Advanced Numerical Analysis Techniques